Little class of one : the lover's A.B.C. - Herbert, Victor, 1859-1924 (M. Witmark & Sons, 1905)
A black and white drawing of curving geometric shapes, forming borders around two irregularly shaped text boxes. Includes a black and white inset portrait photograph of Lew Fields. Dialog song/duet for a male and a female voice. Repetition of the refrain is for SATB chorus.; Title from caption. Advertisements: Songs, Music. 1 female voice & 1 male voice 1 piano This archival material has been provided for educational purposes. Ball State University Libraries recognizes that some historic items may include offensive content. Our statement regarding objectionable content is available at: https://dmr.bsu.edu/digital/about